The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1017/dsj.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary engineering of cyber-physical production systems: highlighting the benefits of a combined interdisciplinary modelling approach on the basis of an industrial case

Abstract: In the context of cross-disciplinary and cross-company cooperation, several challenges in developing manufacturing systems are revealed through industrial use cases. To tackle these challenges, two propositions are used in parallel. First, coupling technical models representing different content areas facilitates the detection of boundary crossing consequences, either by using a posteriori or a priori connection. Second, it is necessary to enrich these coupled technical models with team and organizational mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
0
11
0
1
Order By: Relevance
“…As appropriate tool support is essential for the successful cooperation in and between engineering teams and organisations (Friedl et al 2014;Dotoli et al 2019;Löwen et al 2020;Vogel-Heuser et al 2020a), it should be explicitly modelled. As more tools are being used to exchange knowledge between teams, they need to be integrated or coupled to support such cooperation processes.…”
Section: /30mentioning
confidence: 99%
See 2 more Smart Citations
“…As appropriate tool support is essential for the successful cooperation in and between engineering teams and organisations (Friedl et al 2014;Dotoli et al 2019;Löwen et al 2020;Vogel-Heuser et al 2020a), it should be explicitly modelled. As more tools are being used to exchange knowledge between teams, they need to be integrated or coupled to support such cooperation processes.…”
Section: /30mentioning
confidence: 99%
“…Cyber physical production systems (CPPS) are complex, interconnected, intelligent and innovative product-service systems that require iterative processes and cross-disciplinary as well as cross-company cooperation in all phases of project realisation. Appropriate cooperation, that is, efficient information exchange between multiple interdisciplinary teams, is therefore crucial for the result of the project as inappropriate cooperation may cause delays, cost overruns and quality problems (Vogel-Heuser et al 2020a). Further impeding this challenge, machines and plants as parts of CPPS may operate for more than 30 years and often evolve already during the commissioning and start-up phases deviating from the as-built documentation of the supplier/contractor team (Birkhofer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…capturing conflicts by transformation). Vogel‐Heuser et al [31] have found that inconsistencies can be detected easier with coupled technical models by a priori connections or post hoc tracing considering the perspectives of the collaborative human behaviours. They [32] have also presented the multi‐view collaboration method using knowledge‐base and shown a research demonstrator use‐case, still the method works in model level.…”
Section: State Of the Artmentioning
confidence: 99%
“…Neben dem sich abzeichnenden Trend der CPPS [5] in der Industrieautomatisierung erfordern die zunehmende Volatilität in der globalen und lokalen Wirtschaft, die Verkürzung der Innovations-und Produktlebenszyklen sowie eine enorm steigende Variantenvielfalt Produktionssysteme, die diesen Anforderungsänderungen gerecht werden [6]. Diese sich ändernden Anforderungen führen dazu, dass die konkreten Zielsetzungen für Produktionssysteme in der Phase des Systementwurfs immer unvorhersehbarer werden.…”
unclassified